Molecular Detection and Characterization of Zoonotic and Veterinary Pathogens in Ticks from Northeastern China - Wei, Feng; Song, Mingxin; Liu, Huanhuan; Wang, Bo; Wang, Shuchao; Wang, Zedong; Ma, Hongyu; Li, Zhongyu; Zeng, Zheng; Qian, Jun; Liu, Quan (Frontiers in Microbiology, 2016)
Tick-borne diseases are considered as emerging infectious diseases in humans and animals in China. In this study, Ixodes persulcatus (n=1699), Haemaphysalis concinna (n=412), Haemaphysalis longicornis (n=390), Dermacentor nuttalli (n=253), and Dermacentor silvarum (n=204) ticks were collected by flagging from northeastern China, and detected for infection with Anaplasma, Ehrlichia, Babesia, and Hepatozoon spp. by using nested polymerase chain reaction assays and sequencing analysis. A. phagocytophilum was detected in all tick species, i.e., I. persulcatus (9.4%), H. longicornis (1.9%), H. concinna (6.5%), D. nuttalli (1.7%), and D. silvarum (2.3%); A. bovis was detected in H. longicornis (0.3%) and H. concinna (0.2%); E. muris was detected in I. persulcatus (2.5%) and H. concinna (0.2%); Candidatus Neoehrlichia mikurensis was only detected in I. persulcatus (0.4%). The Ehrlichia variant (GenBank access number KU921424), closely related to E. ewingii, was found in H. longicornis (0.8%) and H. concinna (0.2%). I. persulcatus was infected with B. venatorum (1.2%), B. microti (0.6%), and B. divergens (0.6%). Additionally, four Babesia sequence variants (GenBank access numbers 862303–862306) were detected in I. persulcatus, H. longicornis, and H. concinna, which belonged to the clusters formed by the parasites of dogs, sheep and cattle (B. gibsoni, B. motasi, and B. crassa). Two Hepatozoon spp. (GenBank access numbers KX016028 and KX016029) associated with hepatozoonosis in Japanese martens were found in the collected ticks (0.1–3.1%). These findings showed the genetic variability of Anaplasma, Ehrlichia, Babesia, and Hepatozoon spp. circulating in ticks in northeastern China, highlighting the necessity for further research of these tick-associated pathogens and their role in human and animal diseases.